PROFESSIONAL DIFFICULTIES OF COACHES IN WORKING WITH QUALIFIED ATHLETES OF HUMANITARIAN AND TECHNICAL UNIVERSITIES - Gagieva, Z.A.; Khamikoev, A.A.; Ryzhkin, N.V.; Ezhova, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study, generalize and offer coaches ways to overcome professional difficulties in working with qualified athletes of humanitarian and technical universities. Methods and structure of the study. As part of the study, which was conducted during 2021-2022, a questionnaire was developed to study and justify the difficulties encountered in the professional activities of coaches when working with qualified athletes who are university students. The experiment was carried out at the North Ossetian State University after K.L. Khetagurov (Vladikavkaz) and Don State Technical University (Rostov-on-Don). In total, 25 highly qualified trainers took part in the survey. Results and conclusions. Based on the study, general pedagogical and special requirements for a coach were drawn up, by fulfilling which he will be able to avoid many of the difficulties that arise when working with qualified student athletes in humanitarian and technical universities.